1998
DOI: 10.1038/sj.ijo.0800559
|View full text |Cite
|
Sign up to set email alerts
|

Is there a relationship between leptin and insulin sensitivity independent of obesity?A population-based study in the Indian Ocean nation of Mauritius

Abstract: and 7 WHO Of®ce, Port Louis, Mauritius OBJECTIVE: It has been shown previously in smaller studies that fasting serum leptin and insulin concentrations are highly correlated, and insulin sensitive men have lower leptin levels than insulin resistant men matched for fat mass. We have examined the association between insulin resistance (assessed by fasting insulin) and leptin after controlling for overall and central adiposity in a population-based cohort. DESIGN: Leptin levels were compared across insulin resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
59
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 28 publications
(40 reference statements)
9
59
0
2
Order By: Relevance
“…Leptin, a strong correlate of insulin level and obesity, 3 was highly correlated with only one of three identi®ed factors in this analysis. This factor was characterized mainly by high loadings for overall adiposity (BMI), greater central body fat distribution (WHR), hyperinsulinaemia, triglycerides and HDL-cholesterol.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Leptin, a strong correlate of insulin level and obesity, 3 was highly correlated with only one of three identi®ed factors in this analysis. This factor was characterized mainly by high loadings for overall adiposity (BMI), greater central body fat distribution (WHR), hyperinsulinaemia, triglycerides and HDL-cholesterol.…”
Section: Discussionmentioning
confidence: 97%
“…2 It is generally believed that hyperinsulinaemia andaor insulin resistance underlie this clustering. 1 Leptin, the product of the ob gene, has been observed to be closely correlated with insulin levels, independently of obesity, in a range of populations; 3 and in a study of Polynesian Samoans was also independently associated with key variables of the Metabolic Syndrome. 4 These observations prompted the suggestion that leptin may underlie the Metabolic Syndrome, or at least be an additional component.…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that leptin was not correlated with insulin sensitivity (by intravenous glucose tolerance test) after adjusting for body fat mass by DEXA in African ± American women. 36 On the other hand, a study with 2537 subjects from different races (Asian Indians, Creoles and Chinese) by Zimmet et al 15 showed that insulin resistance was related to leptin concentration regardless of gender or degree of obesity. Nyholm et al 37 also reported that leptin was independently related to insulin sensitivity (hyperinsulinaemic euglycaemic clamp) after adjusting for body fat percentage in Danish men and women.…”
Section: Discussionmentioning
confidence: 99%
“…Two reports from Mauritius and Western Samoa suggested that leptin is associated with insulin sensitivity as measured by the Homeostatic Model Assessment (HOMA) both in men and women. 14,15 However, no relationship has been shown between metabolic syndrome X and leptin in postmenopausal women. 16 By employing a hyperinsulinaemic euglycaemic clamp, Kennedy et al 12 recently found that hyperleptinaemia is associatd with insulin resistance in men but not in women.…”
Section: Introductionmentioning
confidence: 99%
“…At each level of BMI, and in both men and women, there was a highly signi®cant increase in mean leptin concentrations with increasing levels of fasting insulin. 12 …”
Section: Insulin Resistancementioning
confidence: 99%